Dynamic response analysis of concrete box subgrade under double-line heavy-haul railway - Jinglei Liu; Yinghui Jin; Bo Zhao; Aixian Qin; Min Zhao; Jing Guo; Erjun Guo (PLoS ONE, 2026)
The concrete box subgrade, a novel structural form constructed from reinforced concrete to replace conventional fill subgrades, effectively addresses challenges associated with land scarcity and material shortages. A three-dimensional finite element model of the track-subgrade-foundation system was established via numerical simulation to assess the feasibility of the concrete box subgrade. Subsequently, a comparative analysis of dynamic stress, displacement, and acceleration were analysed under three operating conditions: bidirectional operation, unidirectional full load operation, and unidirectional empty load operation. The results reveal that, under moving train loads, dynamic stress is primarily concentrated within the active track zone. Along the vertical webs, dynamic stress initially increases before decreasing, peaking at 1.25 m (one-quarter of the vertical web depth) below the subgrade surface. At a depth of 3.0 m, the dynamic stress attenuation rate of the concrete box subgrade is 1.4 times that of the conventional subgrade, effectively mitigating stress transmission to the foundation. Under bidirectional operation, the maximum dynamic displacement of the concrete box subgrade is 0.203 mm, representing a 92.41% reduction compared to the conventional subgrade, demonstrating enhanced structural integrity and lateral deformation control. The maximum acceleration reaches 0.137 m·s -2 , which is 78.86% lower than that of the conventional subgrade, indicating superior vibration mitigation.